A Case of Fish Sausage Anaphylaxis Induced by Epicutaneous Sensitization to Carmine Contained in Eyeshadows: The Effect of Chelation on Carmine Allergy - Maiko Yamaura; Yuriko Iwahashi; Eri Hashimoto; Jun Miura; Yuri Murayama; Sachiko Koshikawa; Naoko Inomata (Case Reports in Dermatological Medicine)
Carmine is an aluminium and/or calcium-chelated complex form of carminic acid (CA), which is derived from the Dactylopius coccus extract (cochineal), and is globally used as a red-colourant in foods and cosmetics. Although several allergens in carmine allergies, such as CC38K, have been reported, it remains unknown whether chelation affects the allergenicity of carmine. We report a case of Japanese fish sausage (Gyoniku Sausage) anaphylaxis induced by epicutaneous sensitization to carmine contained in eyeshadows. In addition, we report on the effect of chelation on carmine allergy. A 32-year-old woman had experienced itching, wheals, and swelling of her eyelids immediately after applying pink eyeshadows, which contained carmine, on several occasions for 3 years. Two months ago, she developed itching, wheals, and swelling on her whole body, especially her eyelids, and dyspnea immediately after ingesting fried pink fish sausages, which contained cochineal. In skin prick tests (SPTs) with all ingredients ingested in the two episodes of anaphylaxis, only fish sausage was positive. SPT was also positive for carmine. In IgE-immunoblotting using the eyeshadow and fish sausage, the patient serum IgE was bound to three protein bands at approximately 86, 114, and 130 kDa. In addition, IgE-immunoblotting using the carmine showed a broad band at 86–130 kDa, which were consistent with those using the eyeshadow and fish sausage, whereas there is no band using CA. Interestingly, the protein bands using the eyeshadow and carmine were diminished by preincubation in the presence of ethylenediaminetetraacetic acid (EDTA) as a chelating agent. The results indicated that the causative allergens of carmine contained in the eyeshadows could be dechelated by EDTA, reducing its allergenicity. In conclusion, carmine contained in cosmetics can cause epicutaneous sensitisation and consequently can induce food anaphylaxis. To prevent sensitisation in carmine allergy, the effect of chelation on allergenicity of carmine should be considered.